Keterampilan Guru SKI Dalam Membuka Dan Menutup Pelajaran Di MTsN 6 Agam - Rajali, Ahmad (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Sakinah Dharmasraya, 2022)
This thesis research is motivated by the problems found in the field, among others, the teacher applies more explaining skills so that the learning objectives are not effective. In accordance with (QS. An-Nahl 16:125) In the learning process, SKI teachers do not seem to elaborate before the lesson begins, SKI teachers very rarely use learning media. Therefore, the author is interested in researching. How the Skills of SKI Teachers in Opening and Closing Lessons at MTsN 6 Agam. This type of research uses a qualitative descriptive approach, namely data in the form of non-numbers such as sentences or photos or sound recordings. The research location is at MTsN 6 Agam which is located on Jl. Kubang Putiah, Kubang Putiah, Banuhampu District, because in this location researchers found problems that needed to be discussed and needed solutions and found teachers who did not apply skills in teaching. With the key information, namely the VIII grade SKI teacher and the supporting informants, namely the Deputy Head of Student Affairs, and Students. To collect data, the writer did observation, interviews, and documentation. After the data was collected, data processing and data analysis were carried out. Furthermore, the technique of guaranteeing the validity of the data is carried out by means of triangulation. The results showed that: 1) the skills of the teacher in opening class VIII at MTsN 6 Agam. a) Attracting students' attention, the teacher is only focused on the material being taught, b). Doing motivation, giving reinforcement to students, c) Giving reference to students regarding the title of the material and the outlines to be studied, 2) Closing. a) Summarize the issues that have just been discussed. Provide opportunities for students to re-explain the lesson, so that other students can understand it, b) Consolidate students on the main things in the lesson concerned so that, c) Organize all activities or lessons that students have learned, d) Provide note assignments, with the help of people parents and evaluate the level of success of children when participating in learning.